A comprehensive description and evolutionary analysis of 22 grouper (perciformes, epinephelidae) mitochondrial genomes with emphasis on two novel genome organizations. - Xuan Zhuang (Public Library of Science (PLoS), 2013)
Groupers of the family Epinephelidae are a diverse and economically valuable group of reef fishes. To investigate the evolution of their mitochondrial genomes we characterized and compared these genomes among 22 species, 17 newly sequenced. Among these fishes we identified three distinct genome organizations, two of them never previously reported in vertebrates. In 19 of these species, mitochondrial genomes followed the typical vertebrate canonical organization with 13 protein-coding genes, 22 tRNAs, two rRNAs, and a non-coding control region. Differing from this, members of genus Variola have an extra tRNA-Ile between tRNA-Val and 16S rRNA. Evidence suggests that this evolved from tRNA-Val via a duplication event due to slipped strand mispairing during replication. Additionally, Cephalopholisargus has an extra tRNA-Asp in the midst of the control region, likely resulting from long-range duplication of the canonical tRNA-Asp through illicit priming of mitochondrial replication by tRNAs. Along with their gene contents, we characterized the regulatory elements of these mitochondrial genomes' control regions, including putative termination-associated sequences and conserved sequence blocks. Looking at the mitochondrial genomic constituents, rRNA and tRNA are the most conserved, followed by protein-coding genes, and non-coding regions are the most divergent. Divergence rates vary among the protein-coding genes, and the three cytochrome oxidase subunits (COI, II, III) are the most conserved, while NADH dehydrogenase subunit 6 (ND6) and the ATP synthase subunit 8 (ATP8) are the most divergent. We then tested the phylogenetic utility of this new mt genome data using 12 protein-coding genes of 48 species from the suborder Percoidei. From this, we provide further support for the elevation of the subfamily Epinephelinae to family Epinephelidae, the resurrection of the genus Hyporthodus, and the combination of the monotypic genera Anyperodon and Cromileptes to genus Epinephelus, and Aethaloperca to genus Cephalopholis.